TINGKAT SELF-REGULATED SISWA MELALUI PENERAPAN STRATEGI TANDUR PADA PEMBELAJARAN FISIKA KELAS XI IPA SMAN 1 GAUNG INDRAGIRI HILIR. - Hassanah, Piddina; ', Azizahwati; Rahmad, M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed determine the increase of student’s self-regulated in physics learning through applying the TANDUR strategies on subject elasticity and hooke’s law. The method used in this research was quasi experimental method with non-equivalent control group design. This study was taken place in SMAN 1 Gaung Indragiri Hilir with the sample of research consisted of 61 XI IPA grade students in the school year of 2016/2017 who devided become two classes, exsperiment and control class. The instrument data collection in this study is questionnaire of self-regulated which consists of 24 statements. Analysis of the data in this study is descriptive analysis to categorize the average score of student’s self-regulated and analysis of the increase (gain) based on the result of pretest and postest. Based on data analysis, the result of this study obtained an average score of student’s self-regulatedin the experiment class and control class are in high category. For pretest’s score in experiment class, the average Score of 2,36 and control class is 2.37. For score of postest in experiment class, the average Score of 2,95 and control class is 2,60. As for the increase (gain) the average score of student’s self-regulated in the experiment class in medium category with a value of 0,36 and control class in low category with a value of 0,14. This result show the use of TANDUR strategies in physics learning on the elasticity and hooke’s law subject can increase student’s self-regulated.Key Words: Self-Regulated, TANDUR Strategies, Elasticity And Hooke’s Law.